Lending Concentration, Bank Performance and Systemic Risk : Exploring Cross-Country Variation - Beck, Thorsten; De Jonghe, Olivier (World Bank, Washington, DC, 2013)
Using both market-based and annual report-based approaches to measure lending specialization for a broad cross-section of banks and countries over the period 2002 to 2011, this paper is the first to empirically gauge the relationship between bank lending specialization and bank performance and stability in an international sample. Theory suggests that banks might benefit from specialization in the form of higher screening and monitoring efficiency, while a diversified loan portfolio might also enhance stability. This paper finds that sectoral specialization increases volatility and systemic risk exposures, while not leading to higher returns. The paper also documents important time, cross-bank, and cross-county variation in this relationship, which is stronger post 2007, for richer countries, countries without regulatory requirements on diversification, banks with lower market power, and banks with more traditional intermediation models.